L’administration Reagan et le régime castriste (janvier 1981-juillet 1982) - Granjon, Marie-Christine (Études internationales)

(untitled) (Institut québécois des hautes études internationales, 1982)
Because of the Cuban presence in Africa (Angola), President Carter put a stop, in November 1978, to the normalization procedures started with Cuba at the commencement of his mandate. The Reagan administration, far from redressing the situation, has worsened it by incessantly accusing and threatening the Cuban government. At the rime of General Haig's resignation as State Secretary on June 26, 1982, his policy of intimidation towards Cuba had failed to keep the Castro's regime in step. Moreover, the American policy has been thwarted by external obstacles — the attitudes of the Cuban and Soviet leaders, the change in the political climate in Latin America (the conflict in the Malvinas) - and by internal causes - blunders, conflicting announcements, incoherent strategies, fluctuating and equivocal appraisals of the situation by the Reagan administration. This administration has alternately advocated a military solution to the Cuban problem and an essentially economic approach to neutralise the castrist influence in the region. Cuba has been at rimes referred to as a sovereign State to be dealt with on a bilateral basis, and at other rimes as a soviet satellite to be handled with the framework of East-West relations. Under the Reagan administration, Cuba has remained more than ever the ideal scapegoat of American leaders faced with a reassessment of the "pax americana" in Central America and in the North-South relations.